2020
DOI: 10.1177/0020764020937716
|View full text |Cite
|
Sign up to set email alerts
|

Mental status of patients with chronic insomnia in China during COVID-19 epidemic

Abstract: Aim: To study the sleep and mental health of chronic insomnia patients in China during coronavirus disease in 2019 (COVID-19) epidemic. Methods: A total of 764 patients with chronic insomnia were included in this study. From 17 January 2020 to 24 January 2020, insomnia, anxiety and physical symptoms were evaluated online, and they were followed up for 4 and 8 weeks. Main outcomes and indicators were assessed using the Pittsburgh Sleep Quality Index (PSQI) and each factor score, the General Anxiety Disorder-7 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
2
20
0
6
Order By: Relevance
“…Life after being infected by COVID-19 is full of complications [53][54][55]. The prevalence of insomnia in Covid-19 positive male patients studied in the current research was similar to the research finding of many other established research findings in recent times [56,57]. On the contrary, there are chances that the quality of sleep is hampered due to the lockdown itself rather than the Covid-19 disease [58].…”
Section: Discussionsupporting
confidence: 83%
“…Life after being infected by COVID-19 is full of complications [53][54][55]. The prevalence of insomnia in Covid-19 positive male patients studied in the current research was similar to the research finding of many other established research findings in recent times [56,57]. On the contrary, there are chances that the quality of sleep is hampered due to the lockdown itself rather than the Covid-19 disease [58].…”
Section: Discussionsupporting
confidence: 83%
“…Psychiatric patients in China were found to show higher rates of anxiety, depression, and stress symptoms compared to the general population (44). Another study from China found insomnia patients had worse sleep latency, sleep duration, and sleep efficiency due to home isolation and insufficient knowledge (43). Due to limitation on mobility, cancer patients in Ghana were unable to engage in activities involving social gatherings, worsening their mental health (41).…”
Section: Disproportionate Impacts On Minorities and Psychiatric Patientsmentioning
confidence: 99%
“…Hal ini terjadi karenya sulitnya membatasi waktu istirahat dan waktu kerja selama masa isolasi di rumah sehingga sulit untuk tertidur saat harus tidur yang berpengaruh buruk terhadap latensi tidur, kontuinitas tidur dan kualitas tidur. Pasien kurang tidur di malam hari dan aktivitas di siang hari terganggu (Yang et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…Sosialisasi akan pentingnya karantina di rumah tetapi tetap berolahraga di dalam ruangan, membuka jendela dan ventilasi ruangan, memastikan keteraparan sinar matahari yang cukup dapat ditempuh dengan telemedicine agar memberi manfaat bagi masyarakat dengan insomnia dan gangguan tidur lainnya selama pandemi COVID-19 (Morin & Carrier, 2020). Beberapa hal dapat dilakukan untuk mengurangi gejala insomnia selama pandemi COVID-19 adalah menerapkan pola tidur yang sehat, pembatasan waktu tidur, terapi perilaku kognitif lainnya dan dikombinasikan dengan metode yang lebih luas (Yang et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified